PSYCHOLOGICAL AND PEDAGOGICAL PRINCIPLES OF THE METHOD OF ENHANCING THE EDUCATIONAL ACTIVITIES OF SECONDARY SCHOOL STUDENTS IN THE ENGLISH LANGUAGE LESSONS. - Alimova, Marina (Журнал иностранных языков и лингвистики, 2021)
The article discusses that the assimilation of knowledge and the formation of skills and abilities through the system of collective actions of students is one of the main tasks in teaching a foreign language. It is necessary to proceed from the fact that among all the motives of educational activity, the most effective is the organization of the communication system in the group. It not only activates mental activity at this stage, but also directs it to the subsequent solution of various tasks, in the future to creative activity. Teaching a foreign language, the teacher develops both thinking and emotions, and other areas of personality. Based on this, in the education and training of students, it is impossible to imagine without purposeful and controlled pedagogical communication using such principles as personal communication, game organization, collective interaction and concentration.